Miscanthus x giganteus role in phytodegradation and changes in bacterial community of soil contaminated by petroleum industry - Nebeská, Diana; Trögl, Josef; Ševců, Alena; Špánek, Roman; Marková, Kristýna; Davis, Lawrence; Burdová, Hana; Pidlisnyuk, Valentina (Ecotoxicology and environmental safety, 2021)
The second generation energy crop Miscanthus x giganteus (Mxg) was cultivated in pots with mixtures of clean and petroleum industry contaminated soil affected by petroleum, Pb, Zn contamination and high salinity. The survival rate reached 100%, nevertheless the biomass parameters were negatively affected even in the lowest proportion of contaminated soil. In the lowest contamination, where the plant grew still quite successfully, C10-C40 degradation was significantly enhanced compared to the unplanted control with degradation of 58 ± 14%. The plant contribution to aliphatics degradation was significantly correlated with biomass, thus it was negligible in higher contamination. A similar pattern was documented in development of the soil bacterial community. The shift in community structure after Mxg cultivation was observed mainly in the soil with the lowest contaminant proportion, though an increase of bacterial diversity in the miscanthus rhizosphere was observed in all cases. Relative abundance of Actinobacteria was reduced on behalf of several less abundant phyla (Verrucomicrobia, Bacterioides, Acidobacteria). The majority of genera identified as potential petroleum degraders (Pseudomonas, Shinella, Altererythrobacter, Azospirillum, Mesorhizobium, Dyella) were more abundant in contaminated soil with miscanthus, suggesting that Mxg could be a promising crop for phytomanagement of petroleum contaminated soils but salt phytotoxicity needs to be mitigated first.
Keywords: Soil salinity; Phytodegradation; Energy biomass; Miscanthus x giganteus; Petroleum pollution; Soil microbial community